Conflict, Jihad, and Religious Identity in Maluku, Eastern Indonesia - Sholeh, Badrus (Al-Jamiah: Journal of Islamic Studies, 2008)
The collapse of Suhartoâs New Order is a starting point of the quest of religious identity for Indonesian Muslims. A lot of radical groups are founded under the umbrella of liberty and democracy. However, many of them have destroyed the structure of democracy and multicultural society. Conflicts of Maluku (and Poso) in 1999-2003 are the best local context of how religious groups (muslims and christians) fighted severely in the name of God. The conflict is also a good case to understand the weakening of state and the involvements of military (para-military) forces in instigating the conflicts, which impacted to thousands people killed, and destroyed the ethnic and religious harmony in the region. This paper will analyse the conflicts of Maluku and compare it to other religious conflicts in Poso, Central Sulawesi and ethnic conflicts in West Kalimantan, Southern Thailand and Southern Philippines. I argue the growth of local nationalism and unstability of States in Southeast Asian regions brings the rise of civil society and paramilitary forces, which challenges the entities of harmony, peace and multiculturalism in the region.